2021
DOI: 10.3390/ijerph182212233
|View full text |Cite
|
Sign up to set email alerts
|

“Nobody Seems to Know Where to Even Turn To”: Barriers in Accessing and Utilising Dementia Care Services in England and The Netherlands

Abstract: Background: Accessing post-diagnostic care can be difficult for people with dementia and their informal carers. Little is known, however, about the determinants of barriers to access, and how these might vary between countries. The aim of this study was to explore potential inequalities in access to formal dementia care services between England and the Netherlands, specifically from more disadvantaged areas. Methods: This was a mixed-methods study, involving semi-structured qualitative interviews and a carer q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 39 publications
(47 reference statements)
3
40
0
Order By: Relevance
“…13 Dementia Care Navigators in England are not available in all areas, as recent evidence indicates. 14,15 Research from the USA highlights the different aspects of a care navigator role, including providing emotional support, tailoring education and resources, and working closely with the clinical team. 16,17 To date, there appears to be little published evidence on DCN services across England, except one report.…”
Section: Introductionmentioning
confidence: 99%
“…13 Dementia Care Navigators in England are not available in all areas, as recent evidence indicates. 14,15 Research from the USA highlights the different aspects of a care navigator role, including providing emotional support, tailoring education and resources, and working closely with the clinical team. 16,17 To date, there appears to be little published evidence on DCN services across England, except one report.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, some PWDs did not perceive a need for support and refused offered interventions. Contrarily, self‐awareness of changes in cognitive function and acceptance of the diagnosis were enablers for uptake of offered interventions (Birtwell & Dubrow‐Marshall, 2018; Field et al, 2019, 2021; Giebel, Robertson, et al, 2021; Noyes et al, 2000; Van't Leven et al, 2019). People who accepted the diagnosis were likely to take responsibility for self‐management of dementia, engage in new activities, learn new skills, maintain social relationships, seek and accept help, and stay open to offered interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Case managers also support and advise GPs with the coordination of healthcare use, since they have a more in-depth knowledge on the available care services [27]. In the free text, we found that some GPs were not aware of their responsibilities and roles when arranging dementia care (Fig.…”
Section: Discussionmentioning
confidence: 98%